2012
DOI: 10.1371/journal.pone.0037728
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin B3 Prevents Articular Cartilage Degeneration and Heterotopic Cartilage Formation in a Mouse Surgical Osteoarthritis Model

Abstract: Osteoarthritis (OA) is a common disease in the elderly due to an imbalance in cartilage degradation and synthesis. Heterotopic ossification (HO) occurs when ectopic masses of endochondral bone form within the soft tissues around the joints and is triggered by inflammation of the soft tissues. Procyanidin B3 (B3) is a procyanidin dimer that is widely studied due to its high abundance in the human diet and antioxidant activity. Here, we evaluated the role of B3 isolated from grape seeds in the maintenance of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
5
32
1
Order By: Relevance
“…While previous studies showed that procyanidins exert a chondroprotective effect in part by suppressing oxidative stress-induced factors [29,30,32], we revealed that procyanidins inhibit VEGF-induced signaling in the articular cartilage of DMM-induced OA mice. VEGF signaling plays a significant role in OA progression, including enhancing expression of pro-inflammatory cytokines and catabolic mediators in chondrocytes [54,70].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…While previous studies showed that procyanidins exert a chondroprotective effect in part by suppressing oxidative stress-induced factors [29,30,32], we revealed that procyanidins inhibit VEGF-induced signaling in the articular cartilage of DMM-induced OA mice. VEGF signaling plays a significant role in OA progression, including enhancing expression of pro-inflammatory cytokines and catabolic mediators in chondrocytes [54,70].…”
Section: Discussioncontrasting
confidence: 57%
“…In animal studies, grape seed extract, rich with procyanidins, reduce ROS activity and expression of matrix metalloproteinases (MMPs) in the articular cartilage of monosodium iodoacetate-induced OA rats [30], and procyanidins extracted from grape seeds ameliorate collagen-induced arthritis (CIA) in mice through regulation of the toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor-κB (NF-κB) signaling pathway [31]. Notably, daily oral administration of procyanidin B3, one of the components of procyanidins, was shown to mitigate OA pathogenesis in mice subject to medial collateral ligament transection and medial meniscectomy by, at least in part, suppressing induced nitric oxide synthase (iNOS) [32]. However, whether procyanidins, procyanidin B2 and procyanidin B3, or other components of procyanidins exert chondroprotective effects via other OA-relevant pathways is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An augmented differentiation index is indicative of the active maintenance of the hyaline phenotype of chondrocytes (36,37). By contrast, an upregulated expression of Col1a1 or a decline in the differentiation index represented the formation of fibrocartilage rather than hyaline cartilage (37,38). The present study revealed that (Figs.…”
Section: Discussionmentioning
confidence: 46%
“…We demonstrated that in the murine meniscectomy model of OA, calcium-containing crystal deposits were formed in the articular space prior to cartilage degradation (see online supplementary figure S1). These crystal deposits were previously identified as hypertrophic calcification,36 ectopic bone,37 mineralised area38 and heterotopic cartilage,39 but their chemical characterisation and their role in OA had never been determined. Starting from 1 month after OA induction, microCT-scan revealed multiple deposits within the joint, detached from bone, so that they could not be considered as osteophytes.…”
Section: Discussionmentioning
confidence: 99%